Disempowering Traditional Spatial Arrangement of Dayak Community: A Case Study of Tumbang Marikoi Village, Central Kalimantan, Indonesia - Tari Budayanti Usop; Sudaryono Sudaryono; M. Sani Roychansyah (Forest and Society, 2022)
The rapid industrialization in the last decades significantly changed the traditional spatial arrangement in Central Kalimantan Island. The indigenous community’s traditional forest lands management and ownership were transferred to oil palm plantations and mining corporations. Therefore, it disempowered the traditional spatial arrangement by changing the community’s living conditions and transforming their livelihood sources from primary (forests) to secondary and tertiary. The disempowered traditional spatial arrangement of the Tumbang Marikoi village community includes a living area with rivers, forests, and dwellings. They access the forest through the village Kahayan Hulu and the Marikoi River. There is no power grid in Marikoi Village, making them depend on a solar-powered energy generation facility for their daily activities, including gardening, gathering forest products, hunting, mining gold, and fishing. This study applied the phenomenological method to explain the traditional spatial disempowerment in Marikoi Village, Central Kalimantan, following corporate plantation powers and mining activities. The results indicated that the palm plantations affected the Dayak community's living space and daily life. Furthermore, the ownership and management of their customary land, enhancing their economic, social, cultural, and religious life, was transferred to large plantations. As a result, the community’s traditional spatial arrangement was disempowered through river silting from soil drilling, cloudy river water, flooding, distant land for income (selling honey, vegetables, rattan, herbal medicine, and other forest wealth), farming restrictions by clearing land and losing sacred areas and ancestral rituals.